Reaction on "Criticism of the article Říčan J. et al. – Comparison of the quality of the teacher made tests with achievement tests and their influence on the success of pupils: case study. Scientia in educatione, 12(2), 2021" - Říčan, Jaroslav; Škoda, Jiří; Hermanová, Viktorie; Barbora (Scientia in educatione, 2022)
The authors react to P. Novotný's criticism (published in number 1 in 2022) of their article "Comparison of the quality of the teacher made tests with achievement tests and their influence on the success of pupils: case study" which was published in Scientia in educatione, 12(2), 2021.